Metabarcoding data analysis revealed the plant dietary variation of long-tailed macaque Macaca fascicularis (Cercopithecidae, Cercopithecinae) living in disturbed habitats in Peninsular Malaysia - Osman, Nur Azimah; Abdul-Latiff, Muhammad Abu Bakar; Mohd-Ridwan, Abd Rahman; Yaakop, Salmah; Karuppannan, Kayal Vizi; Md-Zain, Badrul Munir (Pensoft Publishers, 2022)
The long-tailed macaque ( Macaca fascicularis ) has a wide range in both Peninsular Malaysia and Borneo. Although the primates are especially vulnerable to habitat alterations, this primate lives in disturbed habitats due to human-induced land-use. Thus, this study presents a faecal metabarcoding approach to clarify the plant diet of long-tailed macaques from five locations in Peninsular Malaysia to represent fragmented forest, forest edge, island and recreational park habitats. We extracted genomic DNA from 53 long-tailed macaque faecal samples. We found 47 orders, 126 families, 609 genera and 818 species across these five localities. A total of 113 plant families were consumed by long-tailed macaques in Universiti Kebangsaan Malaysia, 61 in the Malaysia Genome and Vaccine Institute, 33 in Langkawi Island, 53 in Redang Island and 44 in the Cenderawasih Cave. Moraceae (33.24%) and Fabaceae (13.63%) were the most common families consumed by long-tailed macaques from the study localities. We found that habitat type impacted diet composition, indicating the flexibility of foraging activities. This research findings provide an understanding of plant dietary diversity and the adaptability of this macaque with the current alteration level that applies to long-tailed macaque conservation management interest in the future.